Computing-in-memory using voltage-controlled spin-orbit torque based MRAM array. (March 2021) - Shreya, Sonal; Jain, Alkesh; Kaushik, Brajesh Kumar
Abstract: The Computing-in-Memory (CiM) is one of the best solutions to overcome the data transferring limitation between memory and processor. Moreover, spintronics based devices such as spin-transfer torque magnetic memory (STTM) and spin-orbit torque magnetic memory (SOTM) are emerging as viable contenders for CiM applications. SOTM along with their driving CMOS counterparts show a huge reduction in area and add nonvolatility to CiM designs. In this work, energy-efficient CiM working is performed using Voltage-Controlled SOTM (V-SOTM) where logic operations are implemented within the memory array. The operational conditions and working for performing logic within the memory blocks are elaborated in detail. Further, V-SOTM based full adder (FA) for CiM is presented. Performance analysis has been carried out and compared with exiting CMOS, STTM, SOTM based FA. V-SOTM FA shows 53.98% and 2.7% reduction in logic power and data transfer energy, respectively when compared to SOTM based CiM FA. Furthermore, the VCMA voltage variations for V-SOTM FA is carried out that provide performance improvement with varying voltage pulse. Finally, the effect of parametric variations is carried out using Monte Carlo analysis.